Edukasi Kanker Serviks (Skrining, Diagnosa dan Pencegahan) - Ida Baroroh (Jurnal ABDIMAS-HIP Pengabdian Kepada Masyarakat, 2023)
Cervical Cancer is a malignant tumor that grows inside the cervix (the lowest part of the uterus attached to the top of the vagina) that usually affects women aged 35-55 years. Lack of knowledge and public awareness about the dangers of cervical cancer increases the incidence of the disease in Indonesia. Government efforts in tackling cervical cancer include HPV vaccination for the prevention of cervical cancer, but it is not yet possible to provide it to all women for free. Therefore, it is necessary to educate various lines of society, not only housewives but working mothers and husbands must be exposed to information about cervical cancer so that symptoms can be detected as early as possible and improve a healthy lifestyle as a prevention of cancer. The purpose of this community service is to increase mothers' knowledge about Cervical Cancer Education (Screening, Diagnosis and Prevention). The health education methods carried out are (1) Socialization and Licensing (2) Conduct Affirmation and Pre Test (3) Conduct health education on Cervical Cancer Education (Screening, Diagnosis and Prevention) (4) Evaluation of the results of health education activities with Post Test. The results of this health education can increase participants' knowledge and understanding of the importance of reproductive health and Cervical Cancer Education (Screening, Diagnosis and Prevention), so that they can better maintain their reproductive health and prevent the occurrence of cervical cancer in reproductive age mothers.